Carbohydrate availability and exercise training adaptation: Too much of a good thing? - Bartlett, J. D.; Hawley, J. A.; Morton, J. P. (European Journal of Sport Science, 2015)
Traditional nutritional approaches to endurance training have typically promoted high carbohydrate (CHO) availability before, during and after training sessions to ensure adequate muscle substrate to meet the demands of high daily training intensities and volumes. However, during the past decade, data from our laboratories and others have demonstrated that deliberately training in conditions of reduced CHO availability can promote training-induced adaptations of human skeletal muscle (i.e. increased maximal mitochondrial enzyme activities and/or mitochondrial content, increased rates of lipid oxidation and, in some instances, improved exercise capacity). Such data have led to the concept of `training low, but competing high` whereby selected training sessions are completed in conditions of reduced CHO availability (so as to promote training adaptation), but CHO reserves are restored immediately prior to an important competition. The augmented training response observed with training-low strategies is likely regulated by enhanced activation of key cell signalling kinases (e.g. AMPK, p38MAPK), transcription factors (e.g. p53, PPARd) and transcriptional co-activators (e.g. PGC-1a), such that a co-ordinated up-regulation of both the nuclear and mitochondrial genomes occurs. Although the optimal practical strategies to train low are not currently known, consuming additional caffeine, protein, and practising CHO mouth-rinsing before and/or during training may help to rescue the reduced training intensities that typically occur when `training low`, in addition to preventing protein breakdown and maintaining optimal immune function. Finally, athletes should practise `train-low` workouts in conjunction with sessions undertaken with normal or high CHO availability so that their capacity to oxidise CHO is not blunted on race day.